Economic Empowerment Mustahiq Village Cimanggu Satu Through the Establishment of Bodies, Amil, Zakat, Infaq, and Shadaqah - Ariansyah Ariansyah; Muhlisin Muhlisin (Journal of Islamic Economy and Community Engagement, 2021)
According to Islamic teachings, poverty is a serious problem that must be given serious attention too. Therefore, Islam explains the problem of poverty and social inequality in detail, both in the aspect of conception and solution. This Community Service Report (PKM) discusses the establishment of Badan, Amil, Zakat, Infaq, and Sadaqah (BAZIS) of Cimanggu Satu Village which aims to empower Mustahiq in Cimanggu Satu Village to further improve their economy by managing funds received from the results of Cimanggu Satu Village. zakat distribution becomes more productive.Keywords : Community Service, empowerment, zakat.